2014
DOI: 10.2147/ijn.s50677
|View full text |Cite
|
Sign up to set email alerts
|

The taming of the cell: shape-memory nanopatterns direct cell orientation

Abstract: We report here that the direction of aligned cells on nanopatterns can be tuned to a perpendicular direction without use of any biochemical reagents. This was enabled by shape-memory activation of nanopatterns that transition from a memorized temporal pattern to the original permanent pattern by heating. The thermally induced shape-memory nanopatterns were prepared by chemically crosslinking semi-crystalline poly(ε-caprolactone) (PCL) in a mold to show shape-memory effects over its melting temperature (T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 46 publications
(49 reference statements)
2
28
0
Order By: Relevance
“…Substrates featured a grooved surface, with grooves 1 μm in width, 300 nm in height and spaced 2 μm apart, that could transition to a flat surface, and it was found that cells lost a significant degree of alignment post-transition (Figure 9A). They then utilized the same polymer to create substrates in which the direction of the grooves would abruptly transition orthogonally to the initial orientation [160]. When the topographical shift was induced, the aligned fibroblasts situated along the temporary pattern direction gradually re-aligned in a perpendicular direction.…”
Section: Dynamic Mechano-structural Cuesmentioning
confidence: 99%
“…Substrates featured a grooved surface, with grooves 1 μm in width, 300 nm in height and spaced 2 μm apart, that could transition to a flat surface, and it was found that cells lost a significant degree of alignment post-transition (Figure 9A). They then utilized the same polymer to create substrates in which the direction of the grooves would abruptly transition orthogonally to the initial orientation [160]. When the topographical shift was induced, the aligned fibroblasts situated along the temporary pattern direction gradually re-aligned in a perpendicular direction.…”
Section: Dynamic Mechano-structural Cuesmentioning
confidence: 99%
“…We have recently reported shape-memory surfaces fabricated from PCL films with on-demand, tunable nano-grooves [28][29][30][31]. The key technology behind these studies is a rational method to control the shape switching temperature because PCL, for example, has a Tm around 60 which is very high for biological experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study showed to tune the direction of aligned cells to a perpendicular direction [19]. However, 90% of cells did not change their direction at 60 min after heating, while surface topographic transition was completed within minutes.…”
Section: Direction Of Cell Orientationsmentioning
confidence: 91%
“…The cell morphology was continuously monitored and imaged using a phase contrast microscope. In our previous work, when cells were seeded on patterns with 2000 nm ridges and 9000 nm grooves, cell alignment was gradually lost with time after heating, and finally cells realigned parallel to the permanent grooves after 36 h [19]. This can be inhibited by the addition of a cytoskeletal inhibitor.…”
Section: Direction Of Cell Orientationsmentioning
confidence: 95%
See 1 more Smart Citation